Cultivating a thrive-style culture: Unpacking the secrets of workplace flourishing in the South African workplace - Rensburg, Christine Janse Van; Isabirye, Anthony K (Edelweiss Applied Science and Technology, 2025)
This study aims to explore workplace flourishing, specifying its conceptual limits, tracking empirical developments, and highlighting challenges and research opportunities. While flourishing at work is progressively endorsed, it lacks conceptual clarity, valid measures, and context-specific research, especially in South Africa’s multicultural, socio-politically complex environment. A systematic literature review was conducted using four databases (Web of Science, SABINET, EBSCOhost, Google Scholar), guided by keywords including: “flourishing,” “well-being,” “culture,” “workplace,” “spirituality,” and “South Africa.” Sources considered eligible included peer-reviewed empirical studies, theoretical papers, and systematic reviews addressing workplace flourishing and associated constructs. Exclusions included duplicates as well as non-English or irrelevant research. This study ensured trustworthiness through double screening, validated critical appraisal tools, multiple-source validation of findings, and backward/forward searching of references. Four key themes emerged: (1) conceptual framework positioning flourishing as a multidimensional construct of emotional, psychological, and social well-being; (2) workplace spirituality as an enabler of meaning, connection, and innovative behaviors; (3) connections among flourishing, engagement, and productivity moderated by organizational culture and leadership; and (4) socio-political, economic, and individual stressors that impede flourishing. The review concludes with recommendations for context-sensitive strategies, policies, and leadership approaches to enhance workplace flourishing, emphasizing the need for culturally grounded frameworks and interventions.